2011
DOI: 10.2168/lmcs-7(2:16)2011
|View full text |Cite
|
Sign up to set email alerts
|

Logical Step-Indexed Logical Relations

Abstract: Abstract. Appel and McAllester's "step-indexed" logical relations have proven to be a simple and effective technique for reasoning about programs in languages with semantically interesting types, such as general recursive types and general reference types. However, proofs using step-indexed models typically involve tedious, error-prone, and proofobscuring step-index arithmetic, so it is important to develop clean, high-level, equational proof principles that avoid mention of step indices.In this paper, we show… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
5

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…ere is a large body of works on logic for logical relations, from the early works by Plotkin and Abadi (1993) to more recent works on logics for reasoning about states and concurrency by Ahmed, Birkedal, Dreyer, and collaborators among others (Dreyer et al 2011(Dreyer et al , 2010Jung et al 2015;Krogh-Jespersen et al 2017). In particular, the IRIS logic (Jung et al 2015) can be seen as a powerful reasoning framework for logical relations, as shown recently by Krogh-Jespersen et al (2017) .…”
Section: Introductionmentioning
confidence: 93%
“…ere is a large body of works on logic for logical relations, from the early works by Plotkin and Abadi (1993) to more recent works on logics for reasoning about states and concurrency by Ahmed, Birkedal, Dreyer, and collaborators among others (Dreyer et al 2011(Dreyer et al , 2010Jung et al 2015;Krogh-Jespersen et al 2017). In particular, the IRIS logic (Jung et al 2015) can be seen as a powerful reasoning framework for logical relations, as shown recently by Krogh-Jespersen et al (2017) .…”
Section: Introductionmentioning
confidence: 93%
“…Here, we follow the style of recent łlogicalž accounts of step-indexed logical relations [Dreyer et al 2011[Dreyer et al , 2010Krogh-Jespersen et al 2017;Turon et al 2013], interpreting λ Rust types as predicates on values expressed in a rich program logic (see ğ4 and Challenge #1 below), and interpreting λ Rust typing judgments as logical entailments between these predicates (see ğ7). With our semantic modelÐwhich we call RustBeltÐin hand, the proof of safety of λ Rust divides into three parts:…”
Section: Rustbelt: An Extensible Semantic Approach To Proving Soundnmentioning
confidence: 99%
“…Logical relations and bisimulations. Many semantic techniques have been proposed for reasoning about relational properties such as observational equivalence, including techniques based on binary logical relations [Ahmed et al 2009;Benton et al 2009Benton et al , 2013Benton et al , 2014Dreyer et al 2010Dreyer et al , 2011Dreyer et al , 2012Mitchell 1986], bisimulations [Dal Lago et al 2017;Koutavas and Wand 2006;Sangiorgi et al 2011;Sumii 2009] and combinations thereof [Hur et al 2012[Hur et al , 2014. While these powerful techniques are often not directly automated, they can still be used for verification [Timany and Birkedal 2019] and for providing semantic correctness proofs for relational program logics [Dreyer et al 2010[Dreyer et al , 2011 and other verification tools [Benton et al 2016;Gavazzo 2018].…”
Section: Related Workmentioning
confidence: 99%